Adenosine-A3 receptors in neutrophil microdomains promote the formation of bacteria-tethering cytonemes - Corriden, Ross; Self, Tim; Akong-Moore, Kathryn; Nizet, Victor; Kellam, Barrie; Briddon, Stephen J.; Hill, Stephen J. (Nature Publishing Group, 2013)
The A3‐adenosine receptor (A3AR) has recently emerged as a key regulator of neutrophil behaviour. Using a fluorescent A3AR ligand, we show that A3ARs aggregate in highly polarized immunomodulatory microdomains on human neutrophil membranes. In addition to regulating chemotaxis, A3ARs promote the formation of filipodia‐like projections (cytonemes) that can extend up to 100 μm to tether and ‘reel in’ pathogens. Exposure to bacteria or an A3AR agonist stimulates the formation of these projections and bacterial phagocytosis, whereas an A3AR‐selective antagonist inhibits cytoneme formation. Our results shed new light on the behaviour of neutrophils and identify the A3AR as a potential target for modulating their function.